The impacts of Seri Tanjung Pinang coastal reclamation on the social economy of the community in Tanjung Tokong, Penang - Nadzhirah binti Mohd Nadzir (Kulliyyah of Architecture and Environmental Science, 2015)
The value of a coastal area is significant not only as economy resources but also as environmental safety measure it provides. However, coastal area is very sensitive to any imposed humans' development and its alteration not only affects the environment but also local community. The impacts of coastal reclamation can be seen not only to the environment but are being felt on much larger scale to the extent of socio economy of the community. This research draws literatures on the impacts of coastal reclamation from the socio economy point of views. This study aimed to investigate the impacts of coastal reclamation on the socio economy components of the community in Tanjung Tokong, Penang. It identified the affected socio economy components of the Tanjung Tokong community. Furthermore, the research investigates the most significant impact among the identified components. Apart from it, this research will propose policies on minimizing the impact of coastal reclamation to the communities' socio economy. This research adopted the Socio-economy Impact Assessment (SEIA) approach, whereby the components includes demography, employment and income, residential, public facilities and service, aesthetic quality, quality of life and sense of belonging. The research methodology engages qualitative and quantitative methods consist of review of literature, questionnaire survey and interviews. The data collected from the questionnaire survey was analyzed using Statistical Package for Social Science (SPSS) and interviews adopted Kruger's framework analysis. Among the analysis used were Crosstabulation and Spearman's Rank Order Correlation (rho). The findings has been able to indicate the significant impacts of coastal reclamation to the Tanjung Tokong community. It shows that among all the variables involved aesthetic quality affected community the most. Finally the research proposed several policies enhancement such as public participation, community database, tourism business and constant observation.